Associations between pre-pregnancy obesity and asthma symptoms in adolescents. Issue 9 (15th August 2011) - Patel, Swatee P; Rodriguez, Alina; Little, Mark P; Elliott, Paul; Pekkanen, Juha; Hartikainen, Anna-Liisa; Pouta, Anneli; Laitinen, Jaana; Harju, Terttu; Canoy, Dexter; Järvelin, Marjo-Riitta
Abstract : Background: The high prevalence of children's asthma symptoms, worldwide, is unexplained. We examined the relation between maternal pre-pregnancy weight and body mass index (BMI), and asthma symptoms in adolescents. Methods: Data from 6945 adolescents born within the Northern Finland Birth Cohort 1986 were used. Prospective antenatal and birth outcome data, including maternal pre-pregnancy weight and BMI, and asthma symptoms in adolescent offspring at age 15–16 years, were employed. Logistic regression analyses were performed to examine the associations between relevant prenatal factors and asthma symptoms during adolescence. Results: Current wheeze (within the past year) was reported by 10.6% of adolescents, and physician-diagnosed asthma by 6.0%. High maternal pre-pregnancy BMI was a significant predictor of wheeze in the adolescents (increase per kilogram per square metre unit; 2.7%, 95% CI 0.9 to 4.4 for ever wheeze; 3.5%, 95% CI 1.3 to 5.8 for current wheeze), and adjusting for potential confounders further increased the risk (2.8%, 95% CI 0.5 to 5.1; 4.7%, 95% CI 1.9 to 7.7, respectively). High maternal pre-pregnancy weight, in the top tertile, also significantly increased the odds of current wheeze in the adolescent by 20% (95% CI 4 to 39), and adjusting for potential confounders further increased the risk (OR=1.52, 95% CI 1.19 to 1.95). Results were similar for current asthma. Furthermore, these significant associations were observed only among adolescents without parental history of atopy but not among those with parental history of atopy. Conclusions: The association demonstrated here between maternal pre-pregnancy overweight and obesity, and asthma symptoms in adolescents suggests that increase in asthma may be partly related to the rapid rise in obesity in recent years.